INFLUENCE OF THE WHOLE-ROCK COMPOSITION ON THE CRYSTALLIZATION OF SODIC AMPHIBOLES (PIEMONTE ZONE, WESTERN ALPS) - Martin, Silvana; Cortiana, Giovanni (Ofioliti, 2001)
The recent discovery of glaucophane and crossite amphiboles in metaophiolites of the Combin Unit (Piemonte zone, north-western Alps, Italy) confirms their Alpine re-equilibration under epidote-blueschist facies conditions. Sodic amphiboles were found in two rock types: i) coarse titanite-rich metabasites derived from original Fe-Ti gabbros, and ii) epidote-rich metabasites derived from MOR basalts. Crystallisation of Fe-glaucophane and crossite in the gabbroderived titanite-rich metabasites was favoured by their high total Fe contents, whereas crystallisation of glaucophane and crossite in the basalt-derived epidote- rich metabasites was favoured by Mg depletion due to sea-floor metasomatism. The comparison of all the analysed sodic-amphibole bearing metabasites s.l. from the Combin Unit shows that the FeOtot/MgO bulk-rock ratios, independently on their intrusive or extrusive origin, ranges between 2 and 3. Therefore, it can be concluded that the growth of sodic amphiboles at peak-conditions around 0.6-0.7 GPa and 350-400 °C typical of the subduction metamorphism is favoured in metabasites by a FeOtot/MgO ratio around 2 to 3.